Compliance with recommended preventive behaviours and restrictions for COVID-19: an exploratory analysis of Italians’ attitudes - Travaini, Guido; Flutti, Emma; Blandi, Lorenzo; Sala, Roberta; Songhorian , Sarah; Caruso, Palmina; Mugellini, Giulia (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: as a reaction to the COVID-19 pandemic, countries all over the world have undertaken wide-scale measures to prevent and limit the spread of the virus. Suggested preventative measures mainly included “lockdown”, social distancing, wearing facemasks, and vaccinations. The success of these measures was widely dependent on the cooperation of citizens. However, people reacted differently to the several types of restrictions and recommendations. Even if the majority followed the rules, others ignored them. This study aims to investigate the reasons for the compliance or violation of the rules developed to fight against the COVID-19 pandemic in Italy. Methods: to answer the research question, the analysis of two different surveys conducted on a representative sample of Italians (N=2000) were conducted and analysed through descriptive statistics. Results: the data collection agreed with published literature. Compliance with rules during emergencies followed diligence and altruistic patterns. Fear of sanctions did not seem to work in relation to rules compliance during emergency situations. The lack of clarity of regulations in terms of complexity or constant changes led to non-compliance even intervening as a neutralization technique. Conclusions: government’s fear-based interventions did not seem to work since Italians tended to adhere to the rules primarily out of respect for legitimate authority. Future research should focus more on the topic of trust in institutions in emergency situations with the aim of highlighting the key points for successful governance, also in terms of rules compliance.